Penerapan Metode Gamifikasi dalam Meningkatkan Motivasi Belajar Mahasiswa pada Mata Kuliah Geometri Analitik Bidang Melalui Aplikasi Kahoot - Ratna Yulis Tyaningsih; Laila Hayati; Ketut Sarjana; Nyoman Sridana; Sudi Prayitno (Griya Journal of Mathematics Education and Application, 2022)
The gamification method is a learning method that combines elements of learning and games. The gamification learning method uses the Kahoot application to capture things that interest students and inspire them to continue learning mathematics. The purpose of this study was to determine the application of the gamification method in increasing student learning motivation in the Field Analytical Geometry course through the Kahoot application. This type of research is qualitative with a research method that is a survey. The survey was conducted through the provision of questionnaires to determine students' learning motivation after applying learning with the gamification method. The results of this study showed that (1) student learning outcomes before and after the gamification method was applied respectively were 64.13 and 83.56, (2) there was an increase in learning outcomes with a percentage increase of 30.3%, (3) learning the gamification method can increase student learning motivation with an average percentage after the action of 85.33% and is included in the very good category. This shows that learning with the gamification method is alternative learning that can increase student learning motivation, so it is hoped that variations in learning like this will make learning mathematics interesting and fun.